Medial patellofemoral ligament reconstruction: a new technique - Maffulli Nicola; Carmont Michael R (BMC Musculoskeletal Disorders, 2007)
Abstract Background Primary patellofemoral dislocations are common. In most patients, non-operative management produces satisfactory outcome. If the dislocation recurs after a trial of rehabilitation, operative intervention is considered, with the aim of restoring the soft tissue anatomy to normal. Ninety four percent of patients suffer a tear to the medial patellofemoral ligament (MPFL) following a patellar dislocation. Results We describe our transverse patella double tunnel technique to reconstruct the medial patellofemoral ligament using a free autologous gracilis or semitendinous graft.